The Good story : exchanges on truth, fiction and psychotherapy - Kurtz, Arabella; Kurtz, Arabella (Viking, New York, 2015)
"The Good Story" is an exchange between a writer with a long-standing interest in moral psychology and a psychotherapist with a training in literary studies. Arabella Kurtz and J.M. Coetzee consider psychotherapy and its wider social context from different perspectives, but at the heart of both their approaches is a concern with stories. Working alone, the writer is in sole charge of the story he or she tells. The therapist, on the other hand, collaborates with the patient in telling the story of their life. What kind of truth do the stories created by patient and therapist aim to uncover: objective truth or the shifting and subjective truth of memories explored and re-experienced in the safety of the therapeutic relationship? The authors discuss both individual psychology and the psychology of the group: the school classroom, the gang, the settler nation where the brutal deeds of the ancestors have to be accommodated into a national story. Drawing on great writers like Cervantes and Dostoevsky and on psychoanalysts like Freud and Melanie Klein, they offer illuminating insights into the stories we tell of our lives
Includes glossary.
Keywords: PSYCHOTHERAPY AND LITERATURE; PSYCHIATRY IN LITERATURE